2021
DOI: 10.1177/1359105321995916
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial interventions for adults with newly diagnosed chronic disease: A systematic review

Abstract: While the need for psychosocial interventions in the early formative period of chronic disease diagnosis is widely acknowledged, little is known about the currently available interventions and what they entail. This review sought to collate existing interventions to synthesize their active ingredients. A systematic search on five electronic databases yielded 2910 records, 12 of which were eligible for this review. Evidence synthesis revealed three broad categories of interventions which used at least two out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 125 publications
0
10
0
Order By: Relevance
“…Most patients were aware of the importance of psychological interventions for the DFU treatment -re ecting a belief in the mind-body connection -although some patients may feel reluctant to participate in psychological interventions due to prejudice or shame, or even because they feel emotionally overwhelmed by the emotional consequences of the disease. Therefore, the moment when the intervention is made available is extremely important [42] Caregivers also highlighted the role of psychological status for successful treatments, determination, positive thinking (T.G.1), and acceptance of the disease (T.G.2), highlighting caregivers' awareness of the importance of psychological intervention to help the patient accept the disease. [46] Patients, especially those from T.G.1, reported that DFU was a source of negative emotions and consequences, such as sadness, anger, revolt, and anguish, living with the fear of amputation and trauma, [8-9, 43] and dealing with the impossibility to work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most patients were aware of the importance of psychological interventions for the DFU treatment -re ecting a belief in the mind-body connection -although some patients may feel reluctant to participate in psychological interventions due to prejudice or shame, or even because they feel emotionally overwhelmed by the emotional consequences of the disease. Therefore, the moment when the intervention is made available is extremely important [42] Caregivers also highlighted the role of psychological status for successful treatments, determination, positive thinking (T.G.1), and acceptance of the disease (T.G.2), highlighting caregivers' awareness of the importance of psychological intervention to help the patient accept the disease. [46] Patients, especially those from T.G.1, reported that DFU was a source of negative emotions and consequences, such as sadness, anger, revolt, and anguish, living with the fear of amputation and trauma, [8-9, 43] and dealing with the impossibility to work.…”
Section: Discussionmentioning
confidence: 99%
“…[8-9, 42-43] Therefore, understandably, psychological interventions had almost a direct, immediate positive effect and an indirect impact on medication adherence, empowering patients to engage in self-care behaviors, and boosting overall mood. [42] Regarding the duration of the changes resulting from interventions, participants' opinions differed in both groups, ranging from effects that only lasted during the session to long-term effects after the end of the intervention. However, T.G.2 patients and caregivers reported longer effects, as most of them expressed that the effect remained over time, and was visible till the present moment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation for the convergence between the two countries might be the universality of the challenges people experience following being diagnosed with a chronic condition as an adult. 30 Older and recent studies involving adults with longer diabetes duration have demonstrated a common and persistent perception of challenges in life with T1D across a variety of settings. 10 Such challenges include for example illness perception, 31 32 change in identity 33 34 and acceptance of and adjustment to T1D.…”
Section: Discussionmentioning
confidence: 99%
“…The potential contributions of psychotherapists to the quality of life of those experiencing physical health issues can be illustrated, for example, in data suggesting that the greatest increase in demand for psychologists through 2030 is expected in hospital settings (IHS Markit, 2018). Despite a significant increase in research examining psychological interventions for those experiencing health concerns (e.g., Akyirem et al, 2021; Law et al, 2019; Lazar, 2010), gaps remain in our understanding of psychotherapy with clients with health concerns, including how physical health is addressed in general psychotherapy settings outside of medical sites, how addressing mental health promotes physical health functioning, and the processes or active ingredients of change. Given the widespread prevalence of physical health issues, we can assume that the majority of clients are experiencing these concerns, even if they are not discussing them in therapy.…”
mentioning
confidence: 99%